Analysis Of Factors Influencing Sexual Behavior In Adolescents At Sma Negeri 1 Tanah Miring - Niece Alce; Eri Puji Kumalasari; Nining Istighosah; Riza Tsalatsatul Mufida (Universitas STRADA Indonesia, 2024)
In adolescence curiosity about sexual problems is essential in the formation of more mature relationships with the opposite sex. The maturity of the sexual function also gives rise to impulses and desires for sexual gratification. To analyze the relationship between adolescent knowledge and family and social support on sexual behavior in SMA Negeri 1 Tanah Miring. The research was conducted on 04-05 December 2024 at SMA Negeri 1 Tanah Miring, Meruake Regency, South Papua. The study used an Analytical Survey research design with a crosssectional approach. With the total sampling technique , 60 samples were obtained. The Chi-Square test was used to determine the relationship between variables. The results showed that there were 28 (45.2%) respondents with sufficient knowledge, 35 (80.8%) respondents received family support, and 10 (7.3%) respondents received social support. There is no relationship between adolescents' knowledge about sex and sexual behavior in adolescents in SMA Negeri 1 Tanah Miring, and there is a relationship between family and social support and sexual behavior in adolescents in SMA Negeri 1 Tanah Miring. It is hoped that the most important parental support is to provide education, as well as good parenting to form the character of the teenager himself.